Metabolic Imaging and Biological Assessment: Platforms to Evaluate Acute Lung Injury and Inflammation - Pourfathi, Mehrdad; Kadlecek, Stephen J.; Chatterjee, Shampa; Rizi, Rahim R. (Frontiers in Physiology, 2020)
Pulmonary inflammation is a hallmark of several pulmonary disorders including acute lung injury and acute respiratory distress syndrome. Moreover, it has been shown that patients with hyperinflammatory phenotype have a significantly higher mortality rate. Despite this, current therapeutic approaches focus on managing the injury rather than subsiding the inflammatory burden of the lung. This is because of the lack of appropriate non-invasive biomarkers that can be used clinically to assess pulmonary inflammation. In this review, we discuss two metabolic imaging tools that can be used to non-invasively assess lung inflammation. The first method, Positron Emission Tomography (PET), is widely used in clinical oncology and quantifies flux in metabolic pathways by measuring uptake of a radiolabeled molecule into the cells. The second method, hyperpolarized 13C MRI, is an emerging tool that interrogates the branching points of the metabolic pathways to quantify the fate of metabolites. We discuss the differences and similarities between these techniques and discuss their clinical applications.